INNOVATIVE STRATEGIES FOR FINANCIAL MANAGEMENT IN PUBLIC SECONDARY SCHOOL IN NIGERIA (Journal of Association of Educational Management and Policy Practitioners, 2024)
Despite the existence of various innovative education financing options and the feasibility of their application in Nigeria, their awareness and exploration has been very limited in the country, education is the cornerstone of a nation’s culture and an absolute necessity for economic prosperity and development. There is hardly any household in this country that is not concerned about the state of our education system particularly the secondary system. This paper title on an Rethinking Strategies for financial management in public secondary school in Nigeria. After the introduction, conceptualization of financial management were discussed and strategic ways for financial management were discussed such strategies like Alternative models, Secondary School management board, management control, strategic-planning, NGOs and community participation, money market, and capital market due process mechanism, adoption of modern management techniques among others are the innovative strategies that a school manger will use in managing financial resources in the schools. This paper also was able to identified some constraints financial management, such as inadequate allocations of fund none involvement of subordinate budget making, unstable cost of materials, corruption, and quark school administrators, also the paper make some suggestion, such as Government should provide adequate funding, Zero tolerance to corruption, accurate data bank, appointment of competent school administrators among other